Interleukin-16 rs11556218 is associated with a risk of osteoporosis in Chinese postmenopausal women. (March 2017) - Ma, Xiaoqing; Chen, Yuan; Zhang, Qinghua; Tian, He; Wang, Jianming; Liu, Sanyun; Wang, Baoliang; Wang, Qian
Abstract: Background: Interleukins (ILs), a multifunctional cytokine, play a fundamental role in inflammatory diseases, as well as in the development of osteoporosis. However, there are no data about the role of IL-16 polymorphism in development of osteoporosis. Patients and methods: In this study, we investigated the association between the IL-16 rs11556218 T/G and rs4072122 C/T polymorphisms respectively, and the risk of osteoporosis among 230 patients with osteoporosis and 230 healthy controls. Serum IL-16 level and its correlation with the IL-16 rs11556218 T/G genotypes were analyzed. Results: Significant differences of genotype distribution were observed between osteoporosis cases and controls at the IL-16 rs11556218 T/G genotypes. Compared with the IL-16 rs11556218 T/G homozygote TT, the heterozygous TG genotype was associated with significantly increased risk for osteoporosis (OR = 2.29, 95% CI = (1.15–3.82), p = 0.026); the GG genotype was associated with increased risk for osteoporosis (OR = 1.84, 95% CI = 1.48–3.97, p = 0.015). TG and GG combined variants that were associated with increased risk for osteoporosis compared with the TT genotype (OR = 1.92, 95% CI = 1.43–4.86, p = 0.023). Moreover, in patients with osteoporosis, there was a correlation between the serum IL-16 and rs11556218 T/G genotype. However, the genotype and allele frequencies of IL-16 rs4072122 C/T polymorphisms in osteoporosis patients were not significantly different from controls. Conclusion: IL-16 rs11556218 T/G genotype was associated with increased risk for development of osteoporosis in Chinese postmenopausal women.